2016
DOI: 10.1111/imj.13222
|View full text |Cite
|
Sign up to set email alerts
|

Utility of surgical lung biopsy in critically ill patients with diffuse pulmonary infiltrates: a retrospective review

Abstract: In this series, DAD was the most frequent pathology. The biopsy result was associated with a change in management in a majority of the subjects, most frequently an escalation of prior empiric therapy. Mortality was high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 8 publications
1
13
1
1
Order By: Relevance
“…In one study, the diagnostic yield of open lung biopsy in the context of patients with hematologic malignancy was reported at 62%. 8 Its effectiveness, defined as the ability to generate a change in therapy, has been very variable among studies with reports that go from 57% to 94% 3,8,12,13 ; the efficacy obtained in the study performed by Papazian et al indicated that none of the patients received steroids prior to the biopsy. 13 A recent meta-analysis that included 95 case series of open lung biopsy reported a change in therapy of 78%, being the most common alterations in the initiation or tailoring of therapy, while discontinuation was seen in 10%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In one study, the diagnostic yield of open lung biopsy in the context of patients with hematologic malignancy was reported at 62%. 8 Its effectiveness, defined as the ability to generate a change in therapy, has been very variable among studies with reports that go from 57% to 94% 3,8,12,13 ; the efficacy obtained in the study performed by Papazian et al indicated that none of the patients received steroids prior to the biopsy. 13 A recent meta-analysis that included 95 case series of open lung biopsy reported a change in therapy of 78%, being the most common alterations in the initiation or tailoring of therapy, while discontinuation was seen in 10%.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of complications reported in the literature is around 30%, in which the most common complication is persistent pneumothorax and initiation or an increase in ventilatory support. 3,8,12 One study reported hemorrhagic shock that required reintervention in 2 out of 76 patients. 12 Furthermore, the meta-analysis by Wong and Walkey reported only one case of perioperative mortality from 512 patients analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 En todos ellos se obtuvo tejido pulmonar en cantidad NCT www.medigraphic.org.mx adecuada para el diagnóstico independiente de la localización dentro del tórax, lo que permitió el inicio de una terapéutica o una readecuación de cambios en el manejo de los pacientes, tal como ha sido reportado. [2][3][4][5][6][7] Ninguno de nuestros pacientes presentó criterios para ventilación mecánica ni intubación endotraqueal previa o posterior a la finalización del procedimiento. Sin embargo, la contribución de la biopsia pulmonar abierta en la mejoría de la sobrevivencia de pacientes con dificultad respiratoria aguda ha sido ampliamente reportada 8-10 y para obtener un beneficio máximo debe ser reservada en pacientes con pronóstico razonable y no en pacientes moribundos.…”
Section: Discussionunclassified